(untitled) (International Journal of Psychiatric Nursing, 2022)
Background- Suicide is the second leading cause of death among 15- 21 years olds globally. Suicide is a serious public health problem, so the prevention among college is a priority. There are several factors that affect the adolescents like- age, education, social class, family, mental health, Area of living, all these factors affect significantly for suicidal behaviour. A study was conducted on adolescent at college of Bareilly for early identification of risk factors which affect for suicide and to prevent these activities through social awareness, teaching and guidance. So, we can save the precious life of young once. Objectives- To assess the factors influencing suicidal behaviour among adolescents in college. To find out the association between factors influencing suicidal behaviour with selected demographic variables, To prepare an informational booklet on prevention measures regarding suicidal behaviour among adolescents. Material and Method- A descriptive approach was adapted. The sample consisted of 60 adolescents of GNM II year. Convenience Sample technique was used to choose the sample. Self administered questionnaire are used for data collection. Informative booklet is prepared for suicidal prevention. Majority of respondents included in the study was 50% were in the age group of 19-20 years, 16.6 % were in 17-18 age group, 26% 21-22 age group and 6.6% 23 -above age group. 13% of respondents were male, while 86% were females. In education 48% respondents were in intermediate, 51% of undergraduate. 66% of respondents were living in urban and 33% were lives in rural.13% were married while 86% were unmarried. 56% of Respondents belongs to nuclear family while 43% belongs to joint family. Respondents also were belonged to lower class, 83% middle class and 13% upper class. 75% were Hindu, 11% Muslim, 8% Christian and 5% were Sikh. Result reveals that there was significant association between demographic variable like age (χ2- 47.78 p -123.59), gender (χ2-50.35 p- 5.99) and marital status (χ2 = 8.04 p- 5.99) and the factors influencing suicidal behaviour among adolescents and there is no association between demographic variable like- education, area of living, type of family, religion, social class and factors influencing suicidal behaviour among adolescents. Interpretation and conclusion- Finding of the study score shows that a study to assess the factors influencing suicidal behaviour was effective in terms of identification of risk factors which influence suicidal behaviour. There are some factors which influence the adolescents for suicide. Proper prevention may decrease the risk of suicidal behaviour. Therefore we can save the precious life.